3D-QSAR STUDIES FOR SOME SCHIFF BASES AGAINST BACTERIAL PATHOGEN - KISHOR ARORA (International Journal of Pharma and Bio Sciences, 2014)
3D QSAR viz. 3 descriptor quantitative structure and activity relationship studies for a series of compounds i.e. Schiff base derivatives using their semi-empirical quantum chemical descriptors and their laboratory reported activities against pathogen viz. .Ralstonia solanaecearum (ITCC NO –B1- 0002 ) have been carried out and reported in the present paper. Graphs between observed and predicted activities, both in the terms of p(MIC)cal and p(MIC) obs. are also being reported on the basis of which this may be concluded that some parameters/descriptors have a positive contribution towards the activity. The method has been proved to be useful tool for such type of studies.